Point-of-care measured serum cholinesterase activity predicts patient outcome following severe burns - Schmidt, Karsten; Živković, Aleksandar; Thiele, Martin; Horter, Johannes; Brenner, Thorsten; Weigand, Markus A.; Kleinschmidt, Stefan; Hofer, Stefan (Burns, 2021)
Risk stratification is of utmost importance in burn therapy. However, suitable bedside biomarkers to evaluate the emerging inflammatory response following burn injuries are missing. Serum cholinesterase (butyrylcholinesterase, BChE) has been shown to be a clinically relevant biomarker in acute inflammatory diseases including burns. In this observational cohort study BChE activity was measured by using point-of-care testing (POCT), a novel method in acute burn care. POCT measurements were performed at emergency room admission (ERA) of 35 patients and repeated 12, 24 and 48 h later. All patients or their legal designees gave informed consent. Patients with burn injuries showed sustained BChE activity reduction following hospital admission. BChE activity correlated negatively with burn injury severity, organ failure severity and intensive care unit resource requirements. BChE activity measured at ERA and 12 h later identified survivors and predicted 28-day patient outcome with noninferior efficacy compared to the abbreviated burn severity index (ABSI) scoring. Finally, POCT-measured BChE activity might complement ABSI scoring and possibly improve early risk stratification in acute burn care therapy.
Available online 11 November 2020
Gesehen am 09.08.2021